Featured organization: International Food Policy Research Institute - Cohen, Marc J. (Asia-Pacific Network for Global Change Research, 1999)
This article summarizes IFPRI's mission and emphasizes its work in the Asia-Pacific region. The article highlights IFPRI's research addressing the relationship between global environmental change and food security and assesses IFPRI's 2020 Vision.